(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to produce a product in the form of a pencak silat learning development model through games for 10th-grade high school students in Kendal Regency. The method used is research and development (Research and Development), referring to the Sugiyono model (2017). Data collection techniques were carried out through observation and questionnaires, while data analysis used descriptive percentage techniques to assess the validity and level of product feasibility based on expert assessments. The validation results in a small-scale trial showed a score of 91% from material and development experts, with a very good classification. The evaluation was carried out based on three aspects, namely affective, cognitive, and psychomotor, all of which were met well. A large-scale trial was conducted in three schools in Kendal Regency, with validation results from each physical education expert showing a score of 96% (very good) from SMA Negeri 1 Singorojo, SMA Negeri 1 Boja, and SMA Negeri 1 Limbangan. Overall, this learning model was declared very feasible to use. In addition, students were able to achieve the objectives of pencak silat learning, namely practicing movement skills and evaluating facts, concepts, and procedures in the context of martial arts.